Keadilan Gender dalam Kewarisan Islam: Kajian Sosiologis Historis - Kususiyanah, Anjar (Al-Mazaahib: Jurnal Perbandingan Hukum, 2021)
This study aims to examine the justice toward women in Islamic inheritance system with a historical-sociological approach. The research method used in this research is descriptive qualitative research as an effort to understand the concepts found in a research process, using content analysis techniques and library research. From this research, it is found that according to the sociological-historical approach, the inheritance of women in Islam is not initially regulated and only applies based on customs. In pre-Islamic times, women did not have inheritance rights, even as inheritance for their closest men. that the revelation of the verse regarding Islamic inheritance did not just appear, but as a response to traditions and problems in pre-Islamic Arab society. The provision for the distribution of inheritance 2:1 is not a courtesy and universal provision. This provision cannot justify that the text is clear. The right or wrong of this provision must be measured to what extent it reflects the value of justice and equality as muhkam and universal principle. The inheritance verse makes the Arab community aware that women are not objects of inheritance; but, instead inheritance subjects like men who have the right to inherit and be inherited. So that the verse about inheritance in Q.S. An Nisa (4): 11-12, this is an effort to improve the position of women in society by adjusting the sosial conditions of society according to the era so that the distribution of inheritance 2:1 is not justice, if, it is synchronized with the current sosial phenomena.